Curcumin Alleviates Singapore Grouper Iridovirus-Induced Intestine Injury in Orange-Spotted Grouper (Epinephelus coioides) - Yue-Xuan Wang; Sui-Feng Xu; Ye-Wen Wang; Yun-Xiang Jiang; Qi-Wei Qin; Shi-Na Wei (MDPI AG, 2023)
Singapore grouper iridovirus (SGIV) is a new ranavirus species in the Iridoviridae family, whose high lethality and rapid spread have resulted in enormous economic losses for the aquaculture industry. Curcumin, a polyphenolic compound, has been proven to possess multiple biological activities, including antibacterial, antioxidant, and antiviral properties. This study was conducted to determine whether curcumin protected orange-spotted grouper (Epinephelus coioides) from SGIV-induced intestinal damage by affecting the inflammatory response, cell apoptosis, oxidative stress, and intestinal microbiota. Random distribution of healthy orange-spotted groupers (8.0 ± 1.0 cm and 9.0 ± 1.0 g) into six experimental groups (each group with 90 groupers): Control, DMSO, curcumin, SGIV, DMSO + SGIV, and curcumin + SGIV. The fish administered gavage received DMSO dilution solution or 640 mg/L curcumin every day for 15 days and then were injected intraperitoneally with SGIV 24 h after the last gavage. When more than half of the groupers in the SGIV group perished, samples from each group were collected for intestinal health evaluation. Our results showed that curcumin significantly alleviated intestine damage and repaired intestinal barrier dysfunction, which was identified by decreased intestine permeability and serum diamine oxidase (DAO) activity and increased expressions of tight junction proteins during SGIV infection. Moreover, curcumin treatment suppressed intestinal cells apoptosis and inflammatory response caused by SGIV and protected intestinal cells from oxidative injury by enhancing the activity of antioxidant enzymes, which was related to the activation of nuclear factor erythroid 2-related factor 2 (Nrf2) signaling. Moreover, we found that curcumin treatment restored the disruption of the intestinal microbiota caused by SGIV infection. Our study provided a theoretical basis for the functional development of curcumin in aquaculture by highlighting the protective effect of curcumin against SGIV-induced intestinal injury.